Construction and validation of a prediction model for early recurrence after catheter ablation in patients with persistent atrial fibrillation based on BNP, Ang Ⅱ, homocysteine, MHR, NLR - Chen, Yuning; Sun, Guojian; Zhu, Zhijun; Shen, Farong (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo explore the feasibility and clinical value of early recurrence prediction model for persistent atrial fibrillation after catheter ablation based on brain natriuretic peptide (BNP), angiotensin Ⅱ(Ang Ⅱ), homocysteine, monocyte-to-high density lipoprotein cholesterol (MHR) and neutrophil-to-lymphocyte ratio (NLR).Methods279 patients with persistent atrial fibrillation who underwent catheter ablation in our hospital from January 2022 to December 2024 were divided into training group (n = 195) and verification group (n = 84) according to the ratio of 7:3. The risk factors were screened by univariate and multivariate Logistic regression analysis, and the nomogram model was constructed, and the effectiveness of the model was evaluated in the verification set.ResultsMultivariate Logistic regression analysis showed that diabetes history, elevated BNP, homocysteine, MHR, NLR and Ang Ⅱ were independent risk factors for early postoperative recurrence (P < 0.05). The C-index index of the nomogram model in the training set and the verification set are 0.803 and 0.846, respectively, and the AUC under the ROC curve is 0.802 (95% CI: 0.685–0.918) and 0.855 (95% CI: 0.736–0.973), respectively.ConclusionThe nomogram prediction model can well predict the early recurrence risk of patients with persistent atrial fibrillation after catheter ablation, and provide a reference for clinical individualized treatment, but it needs further verification by large sample and multi-center research.